Innovative method for deriving residual stress distribution in hot-rolled steel beams - An inverse analysis based on finite element modelling and strain data measured with optical fibres - Karlström, Filip; Ronnby, Borik (My University, 2024)
In this masters project, an innovative method of determining residual stresses in steel beams has been developed. The method is based on an inverse analysis method which utilises finite element modelling and strain data collected with optical fibres to estimate the variables describing the residual stress distribution. The problem solved is of a non-linear type since the material behaviour during loading is nonlinear, resulting in that a direct-search method was used in the inverse analysis. The variables describing the residual stress distribution are therefore derived using a Nelder-Mead optimisation algorithm where the difference between the finite element model’s strains and strains obtained from testing is minimised. The method was tested by performing four point bending tests on six hot-rolled profiles split between three HEA200 and three HEB200 beams. It can be concluded that the method is highly dependent on the quality and amount of test data that can be used. Especially the ability to capture data after the point of yielding is crucial in order to accurately mirror the non-linear behaviour of the material. However, if the data is good enough the method works as expected and will find a suitable residual stress distribution of the specimen’s tested. The accuracy of the method in its current state is however questionable as simplifications made in the FE-model might have significantly affected the result. Several improvements of the method is thereby proposed to make it more accurate and reliable.
Keywords: Residual stress distribution, Inverse analysis, Optical fibres, Hot-rolled steel beam, Nelder-Mead